Profile of Students’ Literature Skills and Responses to Outdoor Learning at Surabaya Submarine Monument in Archimedes Law - Sayyidah Anni'matus Sakdiyah Allathifah; Suliyanah Suliyanah (IKIP Mataram, 2022)
One of education goals in 21st century is to improve students’ literacy skills. While participating in PISA since 2000, Indonesia has always been in the last ten rankings. One of the things that can be studied in scientific literacy is physics, which is a challenge for physics teachers to improve students' physics literacy skills in various ways. Outdoor learning is one of the learning innovations that can be applied to improve students' literacy skills. This paper aims to analyze students’ literacy skills profile and their response to outdoor learning. The tests used have been compiled and validated by two expert lecturers in their fields as well as the questionnaire. This research is quantitative descriptive research with purposive sampling. Data on students’ literacy skills and response was collected then analyzed by percentage of literacy achievement. From the instrument questions distributed, it was found that the literacy results of students were still very low. The competence domain is 48.7%, the knowledge domain is only 10.3%, and the context domain is 30.85%. Meanwhile, from the distributed questionnaires, 80.8% of students agreed that Archimedes' law physics learning was done outdoor learning and 50% of students wanted Archimedes' law lessons at the Surabaya submarine monument.